Endogenous systemic liquidity risk - Jin Cao; Gerhard Illing (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Traditionally, aggregate liquidity shocks are modelled as exogenous events. Extending our previous work (Cao & Illing, 2007), this paper analyses the adequate policy response to endogenous systemic liquidity risk. We analyse the feedback between lender of last resort policy and incentives of private banks, determining the aggregate amount of liquidity available. We show that imposing minimum liquidity standards for banks ex ante are a crucial requirement for sensible lender of last resort policy. In addition, we analyse the impact of equity requirements and narrow banking, in the sense that banks are required to hold sufficient liquid funds so as to pay out in all contingencies. We show that such a policy is strictly inferior to imposing minimum liquidity standards ex ante combined with lender of last resort policy.
urn:nbn:de:hebis:30-56969
Keywords: E5; G21; G28; 330; Liquidity Risk; Free-Riding; Narrow Banking; Lender of Last Resort; Gesamtwirtschaftliche Liquidität; Geldpolitik; Finanzmarktkrise; Transmissionsmechanismus; Geldnachfrage; Geldtheorie; Lender of Last Resort; Theorie